DETERMINANTS OF WOMEN'S LABOR FORCE PARTICIPATION LEVEL IN THE KIDUL BANGLI MARKET - Ni Komang Melia Dharma Yoni; Ni Nyoman Yuliarmi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Women's participation is something that must be taken into account in national development. It is absolutely stated that women have the same rights as men to participate fully in all development activities. This study aims to analyze the influence of husband's income, intensity of traditional and religious activities, number of family dependents and motivation to work simultaneously on women's labor force participation in Kidul Bangli Market, to analyze the influence of husband's income, intensity of traditional and religious activities, number of family dependents. and partial work motivation on female labor force participation in Kidul Bangli Market, to analyze the influence of work motivation in moderating the number of family dependents on the level of female labor force participation in Kidul Bangli Market. The methods used are observation, structured interviews and in-depth interviews. The sample determination method uses non-probability sampling and side purposive sampling so that respondents are selected deliberately based on considerations by taking the entire sample, a total of 90 samples. The data obtained was then processed tabulatedly and continued with descriptive analysis tests, moderated regression analysis, classical assumption tests, simultaneous influence (F-test), and partial influence tests (t-test). The research results show that husband's income, intensity of traditional and religious activities, number of family dependents and work motivation simultaneously influence the level of female labor force participation in Kidul Bangli Market. Husband's income and the intensity of traditional and religious activities partially have a negative and significant influence on the level of female labor force participation in Kidul Bangli Market. The number of family dependents partially has a positive and significant effect on the level of female labor force participation in Kidul Bangli Market. Motivation to work as a moderating variable that strengthens the influence of the number of family dependents on the level of female labor force participation in the Kidul Bangli Market.